Commentary: advances in the pharmacotherapy of NASH—anti‐diabetic drugs and beyond. Issue 1 (18th December 2019) - Horn, Paul; Newsome, Philip N.
Abstract : THIS IS A SPECIAL COMMENTARY ON " METFORMIN IN THE TREATMENT OF PATIENTS WITH NON‐ALCOHOLIC STEATOHEPATITIS " BY UYGUN, A., KADAYIFCI, A., ISIK, A.T., OZGURTAS, T., DEVECI, S., TUZUN, A., YESILOVA, Z., GULSEN, M., AND DAGALP K., ORIGINALLY PUBLISHED IN AP&T IN 2004. DOI:10.1111/J.1365-2036.2004.01888.x